Sistema eletrônico de aquisição de sinais de um eletrocardiograma - Vilela, Letícia Michele Dal’Cól [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
Electrocardiography is a health examination in the area of cardiology in which it is recorded the variation of the electrical potentials generated by the electrical activity of the heart, the Electrocardiogram (ECG). To perform this examination, electrodes are placed at specific points on the body in order to record the electrical activity caused by the variation in the cytosolic concentration of calcium, sodium and potassium ions. Subsequently, the diagnosis is made by the information of peak of waves and intervals of time of the obtained signal. The ECG can be obtained in a non-invasive way (external to the human body), with safe and low cost, and has as main advantage to provide quick and accurate information for analysis and diagnosis of cardiovascular anomalies. Once this electrical activity results in small amplitude waves (from 0.5 to 4 mV) and low frequency (0.05 to 100 Hz), the signal reading becomes prejudiced, because it is affected by multiple interference source. In the technical point of view, the instrumentation required for the acquisition, amplification and conditioning of the ECG signal consists in the classical pratical example in a instrumentation system. The system developed for the cardiac electrical activity acquisition consists in the utilization of electrodes, that are connected obeying the principle of Einthoven’s three derivations; instrumentation amplifier, INA 121; and finally the fourth Bessel topology, Notch and bandpass filters for noise removal, aiming the 0.5 Hz to 40 Hz monitoring. In these cases were utilized the operational amplifier LM 741. The instrumentation amplifier was utilized maintaining the elevated impedance input, elevated rejection to common mode signals, in addition to an adjustable differential gain, however in this case, the adopted gain is 100 V/V. The Notch filter was implemented for the removal of the 60 Hz noise from electric network and the bandpass filter for removal of the base line oscillation, in addition to biologic interference.

A eletrocardiografia é um exame de saúde na área de cardiologia no qual é feito o registro da variação dos potenciais elétricos gerados pela atividade elétrica do coração, o eletrocardiograma (ECG). Para executar este exame, eletrodos - são colocados em pontos específicos do corpo para registrar a atividade elétrica causada pela variação na concentração sistólica de íons de cálcio, sódio e potássio. Posteriormente, o diagnóstico é realizado pelas informações de pico de ondas e intervalos de tempo dos sinais obtidos. O ECG pode ser obtido de maneira não invasiva (externo ao corpo humano), segura e de baixo custo, e que tem como principal vantagem fornecer rápidas e precisas informações para análises e diagnósticos de anomalias cardiovasculares. Uma vez que esta atividade elétrica resulta em ondas de pequena amplitude (de 0,5 a 4 mV) e baixa frequência (0,01 a 200 Hz), a simples leitura da mesma fica prejudicada, pois é afetada por diversas fontes de interferência. Do ponto de vista técnico, a instrumentação necessária para a aquisição, amplificação e condicionamento do sinal de ECG constitui o exemplo prático clássico de um sistema de instrumentação. O sistema desenvolvido para a aquisição da atividade elétrica cardíaca consiste na utilização de eletrodos, que são conectados obedecendo o princípio das três derivações de Einthoven; do amplificador de instrumentação, INA 121; e por fim os filtros com topologia Bessel de quarta ordem, Notch e Passa faixa para a remoção de ruídos, visando a monitoração 0,5 Hz a 40 Hz. Nestes casos foi utilizado o amplificador operacional LM741. O amplificador de instrumentação foi utilizado mantendo a elevada impedância de entrada, elevada rejeição a sinais de modo comum, além de um ganho diferencial ajustável, porém neste caso, o ganho adotado é 100 V/V. O filtro Notch foi implementado para a remoção do ruído de 60 Hz proveniente da rede elétrica e o filtro passa-faixa para a remoção da oscilação da linha de base, além da interferência biológica.
Electrocardiogram signal acquisition electronic system
Keywords: Amplificadores eletrônicos; Eletrocardiografia; Engenharia biomédica; Filtros elétricos ativos